THE CHANGES OF THE TESTOSTERONE HORMONE LEVEL DURING PREPUBERTAL PERIODE IN INDUCED HYPOTHYROIDISM RATS - Teguh Budipitojo; Tri Wahyu Pangestiningsih (Jurnal Sain Veteriner, 1998)
The one the influence factors to the normal functions and testes growth is thyroid gland status. The knowledge about the influences of euthyroid, and hypenhyroid to thetesies growth will help to give more understanding of the normal lestes growth. The new born male rats were used todetect the influence of hypothyroidism to the testosterone level during prepubertal periode. Twenty primigravida pregnant rats (Rattus norvegicus albinus) were used. After birth, the male pups were divided inio controls and treatments group. Mothers of the treatment group were given 0,1% 6-n-prapyl-2-thiauracil (PTU), via drinking water, ad libitum, after birth until on day 8. On dary 27, 30, 37, 44, and 51, five control pups and 5 treatment pups were sacrificed. The blood from each pup were collected to detec serum testosteron hormone level using immunoradLometric assay (IRMA) method. The research showed that serum testosteron level ofthe; treated group increased on day 30 (P<0,05) and day 37(P<0,05). Theresultof This research showed that PTU induced hypothyroidism produced increasing serum testosterone level.